Pengaruh Harga, Kualitas Pelayanan, Fasilitas Dan Promosi Terhadap Kepuasan Pelanggan Pada Toko Taqwa Mulya Batanghari Kabupaten Lampung Timur - Wati, Widya; Ratmono, Ratmono (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study examines the effect of price, service quality, facilities and promotions on customer satisfaction which was carried out at Taqwa Mulya Stores Batanghari, East Lamping Regency. Where in the development of the company's sales experienced a drastic decline due to the covid 19 pandemic and the sales target had not yet reached the target. The analytical method used is quantitative research. The object of this research is customers who shop at Taqwa Mulya Bentanghari Store, East Lampung Regency. The total population is 49 respondents. Data collection techniques using literature study, interviews, observations and questionnaires. Data analysis techniques using SPSS 20 include testing the requirements for testing the instrument requirements, testing requirements for analysis and testing hypotheses. The conclusion is that the four variables simultaneously show significant and significant influence on customer satisfaction, so in this case discussing prices, service quality, facilities and promotions on customer satisfaction is very important in a company or organization.Keywords: Price, Service Quality, Facilities, Promotion and Customer Satisfaction.